SYSTEM AND METHOD FOR ADVERTISING GOODS AND SERVICES USING A SHORT IDENTIFYING CODE - AKHLAGHINEJAD, ALIREZA; BASHARDOOST, FARHAD (2008)
A system and method of providing advertising information from a database of advertising listings using a short, easy to remember alphanumeric identifying code associated each listing. The codes are promoted through various known advertising methods. A consumer, upon observing the ad and the code, can obtain additional information regarding the subject matter of the ad by accessing the system and entering the code. The system receives the request and the code from the consumer and transmits the listing of interest to the consumer. In order to keep the codes short while still providing a large number of listings, each code may be associated with multiple listings. The system may filter the listings associated with a requested code using various data, and may also transmit to the consumer a list of such listings from which the consumer may select the listing of interest. L'invention concerne un système et un procédé destinés à fournir des informations publicitaires à partir d'une base de données de listings publicitaires au moyen d'un code d'identification alphanumérique court et facile à mémoriser. Les codes sont mis à disposition par diverses méthodes publicitaires connues. Un consommateur, en regardant la publicité et le code, peut obtenir des informations supplémentaires sur le sujet en accédant au système et en entrant le code. Le système reçoit la demande et le code du consommateur et lui transmet le listing d'intérêt. Pour maintenir des codes courts et fournir en même temps un grand nombre de listings, chaque code peut être associé à des listings multiples. Le système selon l'invention peut filtrer les listings associés à un code demandé au moyen de données diverses, et il peut également transmettre au consommateur une liste des listings disponibles dans laquelle ce dernier pourra choisir celui qui l'intéresse.